The British Journal of Aesthetics. (Londen : British Society of Aesthetics, 1960)
Founded in 1960, the British Journal of Aesthetics is highly regarded as an international forum for debate in philosophical aesthetics and the philosophy of art. The Journal is published to promote the study and discussion of philosophical questions about aesthetic experience and the arts. (https://academic.oup.com/bjaesthetics/issue)
Https://academic.oup.com/bjaesthetics/issue (login)
Engels
Tijdschriften
Keywords: esthetica